1997
DOI: 10.1007/bf02471913
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three commercial media for direct identification and discrimination ofCandida species in clinical specimens

Abstract: One hundred and ninety-two clinical specimens were used to compare the three chromogenic media Albicans ID, Candiselect, and CHROMagar Candida to a standard method using a Sabouraud-chloramphenicol agar medium and standard methods for identification of yeasts. The detection rates were 83.79, 83.24, 86.59 and 84.91% respectively. For the chromogenic media, the rates of direct identification (growth plus specific pigmentation) for Candida albicans were 56.50, 37.68 and 11.59% after 24 hours' incubation and 92.75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 13 publications
2
14
0
1
Order By: Relevance
“…The difference was statistically significant (P ϭ 0.003), and the blue staining was stronger after 24 h of culture on CAID. These results are consistent with those of other investigators (3,5,6,8). The nonpigmented C. albicans isolates usually grew as abundant cultures with confluent colonies which more often remained white on CS than on CAID.…”
supporting
confidence: 92%
“…The difference was statistically significant (P ϭ 0.003), and the blue staining was stronger after 24 h of culture on CAID. These results are consistent with those of other investigators (3,5,6,8). The nonpigmented C. albicans isolates usually grew as abundant cultures with confluent colonies which more often remained white on CS than on CAID.…”
supporting
confidence: 92%
“…CSAM has also been used for the detection of S. aureus nasal carriage: Laudat et al only 22 with blood agar plates. Higher-than-normal detection rates have also been described with several other chromogenic media designed for urinary tract pathogens, C. albicans, and salmonellae (1,5,10,11).…”
Section: Discussionmentioning
confidence: 92%
“…Per the package insert for CHROMagar Candida, the product identifies C. albicans by growth as light to medium green colonies, C. tropicalis by growth as steel blue colonies accompanied by purple pigment diffusion into surrounding agar, and C. krusei by growth as large, fuzzy, rose-colored colonies with white edges, all after incubation for 48 h at 37°C. This media has been demonstrated to identify C. albicans, C. krusei, and C. tropicalis in several studies (3,(6)(7)(8)(9)(10)(11)(18)(19)(20). Recent reports have suggested that the dark green appearance of Candida dubliniensis can also be reliably distinguished from that of C. albicans (12,13,15,19).…”
mentioning
confidence: 95%
“…The colonies are sometimes accompanied by a diffusion of pigment into the surrounding agar (9). Other authors consider the media unreliable for the identification of C. glabrata (5,10,8,14,18,19).…”
mentioning
confidence: 99%